Epidemiology, Treatment Patterns, and Cost Analysis of Immune Thrombocytopenia in Spain between 2014 and 2020: A Population-based Study - González-López, Tomás J.; Alperovich, Gabriela; Burillo, Elena; Espejo-Saavedra Soler, Marta; Rebollo-Gómez, Elena; Hernández, Ignacio; Justicia, Jose L.; Lozano, María L. (TH Open, 2024)
Background Immune thrombocytopenia (ITP) is characterised by low platelet counts and often leads to bleeding, fatigue, and reduced health-related quality of life.Methods This observational, retrospective, population-based study using BIG-PAC® database included Spanish paediatric and adult patients with primary ITP diagnosed in primary care and hospitals between 2014 and 2020 (median follow-up: 4 years). Epidemiology, baseline/clinical characteristics, treatment trends, healthcare resources and costs were analysed.Results The BIG-PAC® database contains records of 1,818,588 patients; 170 adults and 27 children with ITP were included in our analysis. ITP prevalence and annual incidence per 100,000 were estimated in 10.8 (2.8 in chronic ITP [cITP] patients) and 1.5 (0.3 in cITP patients), respectively. Epistaxis was the most common bleeding event, followed by genitourinary and gastrointestinal bleeding; >50%/> 75% of ITP/cITP patients reported fatigue. Chronic patients had lower platelet counts at baseline and required more transfusions. Corticosteroids, immunosuppressants, and thrombopoietin receptor agonists were the most used agents in first-, second- and third-line treatment, respectively. Thirty-five patients, all of them in chronic phase, underwent splenectomy. Patients had on average 13.9, 6.6, and 1.2 visits/year to primary care, haematology/internal medicine, and emergency departments, respectively. More than one-fourth of adult patients took on average 16.3 days of sick leave annually. Mean annual total health care costs were €10,741 (ITP patients) and €19,809 (cITP patients).Conclusion This is the first study to provide an overall perspective on the situation of the Spanish ITP population in terms of epidemiology, treatment trends, health care resources and costs, highlighting unmet patient needs, and direct and indirect costs/resource use between 2014 and 2020.
Keywords: primary immune thrombocytopenia; adult; paediatric